Balloon kyphoplasty treatment for a spontaneous vertebral fracture in renal osteodystrophy. (12th May 2011) - Demetriades, Andreas; Wong, Fabian; Ellamushi, Habib; Afshar, Fari; Yeh, John
Abstract : Renal osteodystrophy is a spectrum of musculoskeletal abnormalities. Bony fractures can occur spontaneously or with minor trauma in this condition. The authors report the first case of balloon kyphoplasty treatment for painful renal osteodystrophy vertebral body collapse secondary to end-stage renal failure on dialysis. The authors have demonstrated that kyphoplasty is a safe procedure for pain management in severe dystrophic patients. In addition, pain treatment with kyphoplasty can be achieved without anatomical restoration of vertebral body height.